BUDIDAYA JAMUR PERUSAK KAYU IV. KULTUR JAMUR PADA SUBSTRAT SERBUK GERGAJI YANG DIPERKAYA - Sihati Suprapti; Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1988)
Oyster  mushroom (Pleuroius ostreatus) has been cultivated on five sawdust  media  of  five wood  species, i.e. durian (Durio  zibethinus Murr.),  jeungjing  (Albizia  falcataria  (L.)  Fosb.).  manii (Maesopsis eminii Engl.),  rubber  (Hevea brasiliensis Muell.  Arg.)  and  coconut   (Cocos  nucifera  L.). The  composition  of  the  media  was 100  % saw dust, 80 % sawdust + 20 % rice  bran,  99.5 % sawdust  +  0.5 % lime,  99 % sawdust + 0.5 % lime + 0.5 % trisuperphosphate    (TSP),  and 97.5 % sawdust + 0.5 % lime  +  0.5 %  TSP + 1.5 % gypsum.  Each  media was mixed  with sufficient distilled water. The  media  was allowed to cool after  autoclave  sterilization   before  being  inoculated   with  pure  culture  of  the  mushroom.   The  mature  mushroom was harvested  daily  after  the growth  of  fruiting  body.The highest  yield  was obtained  from Rubber wood  (129.8 g per 600  g media).  The  beat composition was obtained from  sawdust  80  % mixed  with  rice bran 20  % (103.17 g per  600  g media).The  higher  Biological  efficiency  during  the four  month observation were  obtained  from  media  containing  sawdu1t 80  % mixed  with  rice bran  20 %, i.e. rubber (66.73 %),   durian  148.15  %), coconut (28.12 %),  and  manii  (22.38 %).